Modeling and simulation for heavy-duty mecanum wheel platform using model predictive control - Fuad, A. F.M.; Mahmood, Iskandar Al-Thani; Ahmad, Salmiah; Norsahperi, N. M.H.; Toha, Siti Fauziah; Akmeliawati, Rini; Darsivan, Fadly Jashi (IOP Publishing, 2016)
This paper presents a study on a control system for a heavy-duty four Mecanum wheel platform. A mathematical model for the system is synthesized for the purpose of examining system behavior, including Mecanum wheel kinematics, AC servo motor, gearbox, and heavy duty load. The system is tested for velocity control, using model predictive control (MPC), and compared with a traditional PID setup. The parameters for the controllers are determined by manual tuning. Model predictive control was found to be more effective with reference to a linear velocity